2021
DOI: 10.5194/egusphere-egu21-14898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Didymos Gravity Science Investigations through Ground-based and Inter-Satellite Links Doppler Tracking

Abstract: <p>The Asteroid Impact and Deflection Assessment (AIDA) is an international collaboration supported by ESA and NASA to assess the feasibility of the kinetic impactor technique to deflect an asteroid, combining data obtained from NASA’s DART and ESA’s Hera missions. Together the missions represent the first humankind’s investigations of a planetary defense technique. In 2022, DART will impact Dimorphos, the secondary of the binary near-Earth asteroid (6580… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In order to derive a realistic model of the systemʼs evolution, both of these effects require an excellent knowledge of the masses of the bodies involved. This knowledge will be acquired via the RSE with Hera, involving the main spacecraft and the CubeSats (Tortora et al 2019(Tortora et al , 2020Zannoni et al 2020;Tortora et al 2021). However, to determine the YORP and BYORP effects, a key observable is the one coming from spacecraft angular measurements, where the novel WBDDOR system will be a key enabling technology boosting the determination accuracy.…”
Section: X-dst For Radio Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In order to derive a realistic model of the systemʼs evolution, both of these effects require an excellent knowledge of the masses of the bodies involved. This knowledge will be acquired via the RSE with Hera, involving the main spacecraft and the CubeSats (Tortora et al 2019(Tortora et al , 2020Zannoni et al 2020;Tortora et al 2021). However, to determine the YORP and BYORP effects, a key observable is the one coming from spacecraft angular measurements, where the novel WBDDOR system will be a key enabling technology boosting the determination accuracy.…”
Section: X-dst For Radio Sciencementioning
confidence: 99%
“…However, while ground-based S/C radio tracking is a well-established technique for relatively large and massive bodies, the use of space-to-space intersatellite links capable of determining the Doppler shift due to the relative line-of-sight velocity between the two bodies would be much more appropriate at small bodies, but this technology has not been explored much. Our previous studies (Tortora et al 2019(Tortora et al , 2020(Tortora et al , 2021Zannoni et al 2020) have shown that the satelliteto-satellite tracking option would ideally complement groundbased radio tracking, providing the best results for both the mass and gravity field determination and S/C positioning. Hera will, for the first time, use a miniaturized and lightweight ISL system, capable of being integrated on nanosatellites weighing a few kilograms.…”
Section: Intersatellite Link For Radio Sciencementioning
confidence: 99%